Issues in Malaysia music industry: a case study / Shahrizal Jamaludin - Jamaludin, Shahrizal (2011)
The music industry as a whole is facing a massive challenge. The nature of the industry has changed as some of the most popular artists, their product life cycle are shorts. Other than that, the market has changed very quickly according through times. The non development of our Malaysian music industry is because there are no cooperation whatsoever from any parties that are willing to gamble and venturing to our music scene as what we all can see nowadays, piracy problems are everywhere and it is hard to barricade. Meanwhile, mass medias and recording companies did not carrying out their responsibilities with righteous because their priority is more to the profit that they will get compare to the quality of works and audience attitude in Malaysia that more emphasizing appearance level more than talent. Malaysian music industry is more of a "stereotype". This is because most artists, musicians and composers who are involved in the music scene are not exposing to the formality of music and that was the reason on why most of their works are invariable. The music industry can be developed in many ways, first of all by finding our own musical identity. Secondly, by changing the way of mass media marketing and last but not least, artists should make quality of their product a priority. So, whatever the arguments and how they respond to such changes are going to be crucial in their success and to continue on developing the music industry as a whole and I hope this research can be helpful to young musicians and composer who want to be involved in the Malaysian music industry.